Efforts to Increase Students’ Islamic Religious Learning Outcomes Through Nasyid in Elementary School - Wahyuni, Sri (Universitas Pahlawan Tuanku Tambusai, 2021)
This research was motivated by initial observations which showed the low learning achievement of Islamic Religion for the rest of class III at SDN 064969. It was proven that only 45% of students' learning achievement of Islam was complete. Because students are bored with the monotonous learning process. So the researcher offers the application of Nasyid. The purpose of this study was to determine 1) the significance of differences in the acquisition of Islamic learning by using nasyid in class III SDN 064969. 2) The interaction between the use of nasyid and learning styles with the acquisition of Islamic learning for third grade students of SDN 064969. The research method used was PTK. . The research was carried out in three cycles, consisting of planning, implementing actions, observing and reflecting. The subjects in this study were the third grade students of SDN 064969 as many as 35 people. The research data were obtained from observation guide sheets, interview guidelines, questionnaires, learning outcomes and field notes. The results obtained from this study are 1) There is a significant difference in the acquisition of learning Islam with nasyid. 2) There is a real interaction between the use of nasyid and learning styles with the acquisition of Islamic learning. Through this research, it is understood that nasyid extracurricular activities help elementary school students in improving Islamic religious education learning outcomes.